TEM investigation of defect structure in GaAlN/GaN heterostructures - Makkai, Zs; Pécz, B.; di Forte-Poisson, M.A. (Vacuum, 2003)
GaAlN/GaN layers are promising candidates as base materials for novel microelectronic devices. The electronic properties of these devices are strongly influenced by the density of threading dislocations, inversion domains and the inverted hexagonal pits on the surface. The effect of the Al concentration in GaAlN on the above defects is the subject of the present paper. It is found that inversion domains and threading dislocations are present in the layers, and inverted hexagonal pyramids are present on the surface. The density of the pits increases with the Al concentration, which is clearly in agreement with the fact that Al segregates to the pits. Above a certain Al concentration, cracks appear in the grown thick GaAlN layers, which can be classified as deep and shallow cracks. The segregated Al increases the strain field in the lattice and leads to the formation of open cracks. Pit formation is connected to inversion domains, which are created on steps in the buffer layer. For the elimination of the V-shaped pits, the formation of inversion domains should be avoided. A set of samples that was realised successfully and both of the pits and the cracks were eliminated by the improved growth technique.